High fructose promotes MYCN-amplified neuroblastoma progression through NgBR-ACSS2-mediated biosynthesis of acetyl-CoA - Wenquan Hu; Xiang Wang; Zhi Fang; Jing Zhang; Munichandra Babu Tirumalasetty; Qing Robert Miao (Cell Reports, 2025)
Summary: MYCN amplification, a characteristic of aggressive neuroblastoma, presents therapeutic challenges. This study uncovered the potential effects of a fructose metabolite, acetate, on the transcriptional regulation of MYCN expression, which is still largely unexplored. We elucidated the pivotal role of acyl-coenzyme A (acyl-CoA) synthetase short-chain family member 2 (ACSS2), found to be heightened in MYCN-amplified neuroblastoma. We demonstrated that ACSS2 enhanced MYCN gene transcription and growth of MYCN-amplified neuroblastoma. Our results revealed a new mechanism wherein ACSS2 orchestrates MYCN transcription by escalating acetyl-CoA levels and histone acetylation, hinting at a metabolic participation in forcibly dictating MYCN regulation. We further demonstrated that fructose or acetate exacerbated neuroblastoma growth, which can be halted by the ACSS2 inhibitor. We further identified the Nogo-B receptor (NgBR) as the trigger for ACSS2 induction through the Akt-SREBP-1 pathway. Our findings propose NgBR as a novel therapeutic target, emphasizing the promising potential of metabolic therapies for managing aggressive MYCN-amplified neuroblastoma.